THE GROUP INVESTIGATION TYPE COOPERATIVE LEARNING MODEL WITH THE ASSISTANCE OF IMAGE MEDIA TO IMPROVE THE LEARNING OUTCOMES OF CLASS VIII STUDENTS AT SMPN SATAP KARANGGI ROWA - Citra Rambu Joru; Yohana Makaborang; Riwa Rambu Hada Enda (JURNAL EDUSCIENCE, 2023)
The purpose of this study was to determine the application of students' cognitive learning outcomes using the Collaborative Group Inquiry (GI) learning model on the material of the human respiratory system in class VIII of SMP Negeri Satap Karanggi Rowani, Umbu Ratu Nggay Barati Tengah District. Sumba. Area The population of this study were all students of class VIII, SMP Negeri Satap Karanggi Rowa, totaling 30 students, and the research sample was class VIII students, totaling 30 students. Multiple choice questions on the pretest and posttest were used to collect data for this study. The results of the vitality survey showed that 17 students scored more than 65 or 57%, while 13 students scored less than 65, namely. 3% of 30 students in the first cycle, and 29 students scored more than 65 points in the second cycle. . or 97%, while 1 student or 3% of 30 students scored below 65. Based on the results of the study it can be concluded that the application of the Cooperative Group Investigation (GI) learning model to the human respiratory system material for SMP Class VIII students Negeri Satap Karanggi Rowa can improve student performance and assessment. problems and can improve student learning outcomes with group inquiry type cooperative learning models.Keywords: Group Learning Model, media images, learning outcomes Abstrak            Tujuan penelitian ini adalah untuk mengetahui hasil belajar kognitif peserta didik dengan penerapan model pembelajaran Cooperative Learning Group Inquiry (GI) pada materi sistem pernapasan manusia di kelas VIII SMP Negeri Satap Karanggi Rowan Kecamatan Umbu Ratu Nggay Barati Kabupaten Sumba Tengah. Populasi penelitian ini adalah seluruh siswa kelas VIII SMP Negeri Satap Karanggi Baris yang berjumlah 30 pesrta didik dan sampel penelitian terdiri dari 30 peserta didik kelas VIII. Dalam penelitian ini digunakan soal pretest dan posttest berupa soal pilihan ganda untuk mengumpulkan data. Hasil survei vitalitas adalah 17 peserta didik yang mendapat nilai lebih dari 65 poin atau 57%, sedangkan 13 dari 30 peserta didik pada siklus I atau 3% dari 30 peserta didik pada siklus kedua, berada di bawah 65. 29 peserta didik mendapat nilai lebih dari 65 poin, atau 97%, bahkan 1 peserta didik mendapat nilai kurang dari 65, atau 3% dari 30 peserta didik. Berdasarkan hasil penelitian dapat disimpulkan bahwa penerapan model pembelajaran Kooperatif Group Study (GI) pada materi Sistem Pernapasan Manusia di Kelas VIII SMP Negeri Satap Karanggi Rowa dapat meningkatkan prestasi dan kemampuan peserta didik. Pemecahan masalah dan dapat meningkatkan hasil belajar peserta didik melalui model pembelajaran Cooperative group research.Kata Kunci: Model Tipe Pembelajaran Kelompok, media gambar, hasil belajar.